Upaya Meningkatkan Kemampuan Motorik Halus Anak Melalui Kegiatan Melipat Pada Kelompok B TK Pertiwi I Donohudan Tahun Ajaran 2014/2015 - Wardani, Dian Kusuma, Dra. Surtikanti, S.H., M.Pd (2015)
Folding activity is interesting and fun method for young children who will develop fine motor skills. The reality that occours in learning activities in kindergarten are many teachers who are still using methods that are tedious to develop fine motor through folding. This research aims to improve fine motor through folding. This research is a classroom action research subjects. The subjects of this study are learners group B in kindergarten Pertiwi I Donohudan year 2014/2015. This research is a classroom action research (car) with the working procedure 2 (two) cycle consists of four stages: planning, action, observation and reflection. The results showed an increase in students' fine motor skills. This study used data cololection methods of observation, field notes and documentation. Research shows that the average child's motor before action is 50,20%. After folding the learning by doing activities in the first cycle of fine motor increased to 60,20%. In the second cycle of fine motor skills of children increased to 83,74%. Overall folded can improve fine motor children in group B in kindergarten Pertiwi I Donohudan.